A 23 bp cyp51A Promoter Deletion Associated With Voriconazole Resistance in Clinical and Environmental Isolates of Neocosmospora keratoplastica - James, Jasper Elvin; Lamping, Erwin; Santhanam, Jacinta; Milne, Trudy Jane; Abd Razak, Mohd Fuat; Zakaria, Latiffah; Cannon, Richard David (Frontiers in Microbiology, 2020)
In the fungal pathogen Aspergillus fumigatus, resistance to azole antifungals is often linked to mutations in CYP51A, a gene that encodes the azole antifungal drug target lanosterol 14α-demethylase. The aim of this study was to investigate whether similar changes could be associated with azole resistance in a Malaysian Fusarium solani species complex (FSSC) isolate collection. Most (11 of 15) clinical FSSC isolates were Neocosmospora keratoplastica and the majority (6 of 10) of environmental isolates were Neocosmospora suttoniana strains. All 25 FSSC isolates had high minimum inhibitory concentrations (MICs) for itraconazole and posaconazole, low MICs for amphotericin B and various (1 to > 32 mg/l) voriconazole susceptibilities. There was a tight association between a 23 bp CYP51A promoter deletion and high (> 32 mg/l) voriconazole MICs; of 19 FSSC strains sequenced, nine isolates had voriconazole MICs > 32 mg/l, and they all contained the 23 bp CYP51A promoter deletion, while it was absent in the ten remaining isolates with low (≤ 12 mg/l) voriconazole MICs. Surprisingly, this association between voriconazole resistance and the 23 bp CYP51A promoter deletion held true across species boundaries. It was randomly distributed within and across species boundaries, and both types of FSSC isolates were found among environmental and clinical isolates. Three randomly selected N. keratoplastica isolates with low (≤ 8 mg/l) voriconazole MICs had significantly lower (1.3 to 7.5 times) CYP51A mRNA expression levels than three randomly selected N. keratoplastica isolates with high (> 32 mg/l) voriconazole MICs. CYP51A expression levels, however, were equally strongly induced ( 6500-fold) by voriconazole in all six strains reaching levels, after 80 min of induction, that were comparable to those of CYP51B. Our results suggest that FSSC isolates with high voriconazole MICs have a 23 bp CYP51A promoter deletion that provides a potentially useful marker for voriconazole resistance in FSSC isolates. Early detection of possible voriconazole resistance is critical for choosing the correct treatment option for patients with invasive fusariosis.